Religious social norms and corporate sustainability: The effect of religiosity on environmental, social, and governance disclosure. (19th October 2020) - Terzani, Simone; Turzo, Teresa
Abstract: This study examines the relationship between religious social norms and corporate sustainability by analyzing the effect of religiosity and religious affiliation on environmental, social, and governance (ESG) disclosure. To this aim an empirical analysis was conducted on a sample of 17, 432 firm‐year observations across 33 countries between 2004 and 2017. A principal component analysis (PCA) was performed in order to estimate a country‐level measure of religiosity, which included the variables "religious person, " "importance of religion, " and "religious service attendance." The results, obtained by means of a country‐weighted random‐effect Tobit regression model, showed a non‐linear, U‐shaped relationship between religiosity and ESG disclosure, and a significantly moderating effect of religious affiliation. Consistent with the "social norm" theory, this study contributes to previous literature on ESG determinants by showing that religiosity and religious affiliation significantly influence companies' attitude toward non‐financial disclosure.